Continuous knowledge contribution behavior in business online communities - Hashim, Kamarul Faizal; Tan, Felix B.; Andrade, Antonio Diaz (2011)
An online community’s (OC) long term success depends on its members’ willingness to stay and continue using the OC. Continuous use of an OC is closely related to knowledge sharing activity. However there is a limited understanding of this behavior especially within business online communities. This paper proposes an integrated approach combining motivational, sociological and technological perspective to model this behavior. The model is grounded in Expectation-Confirmation Theory and the antecedents of this behavior are predicted using Expectancy-Value of Achievement model and Technology Acceptance Model.